Perlindungan Hak Anak dalam Perspektif Hak Asasi Manusia - Fikri Fikri (Kanun Jurnal Ilmu Hukum, 2011)
ABSTRACT: The protection for children rights is absolute right and parents of the children have responsibility to protect their children but if there are no parents or other people who can be responsible for taking care of them; hence the state has to take this duty. The convention regarding children rights aims to improve and protect the interest and children rights as human; therefore they can develop their live mentally, socially and physically. Based on this fact, this paper look at to which extent the law protect their rights in the human rights view. Every child has rights to enjoy health service and social security based on the need of their physic mental and spiritual. Each child has a right to have parents protection, family, community and state. The humankind has to provide to children by the best service. Therefore, the right and the obligation is a cause that cannot be forgotten that it becomes the duty of the adult to provide them the protection. The obligation for them is on their family and this role is recognized by the convention. However, nowadays many of them are not able t depend on their family to enjoy their protection and aid and also ironically the state cannot guarantee this right. Protection of Children Rights in the Human Rights View